From fragmented levels of care to integrated health care: Framework toward improved maternal and newborn health. Issue 2 (11th January 2021) - Barnea, Eytan R.; Nicholson, Wanda; Theron, Gerhard; Ramasauskaite, Diana; Stark, Michael; Albini, S. Mark; Nassar, Anwar H.
Abstract: Worldwide, health systems and care approaches vary widely due to local reality, distance to facilities, cultural norms, resources, staff availability, geography, and politics. Consequently, globally maternal–newborn dyad care and outcomes are highly variable, leading to approximately 800 maternal deaths daily with a 100‐fold difference among high‐ and low‐resource countries. Irrespective of where care is received, maternal safety and wellbeing should be preserved. Despite ongoing efforts, however, this is not the case. Large gaps exist between spending and clinical outcomes. Segmented health care, coupled with poor planning and inadequate resource distribution, results in failure to provide essential life‐saving treatment. The proposed solution is a regional integrated care model from midwife to advanced level III/IV care and the newborn unit, achieved through effective coordination by site, staff, and clinicians. This model has been successfully implemented in high‐ to low‐resource countries in the past 20 years. In the large diverse population of the United States, constructive steps have been implemented to reduce high maternal mortality in black and rural communities. The COVID‐19 pandemic demonstrates the feasibility of rapid resources coordination to provide effective advanced care. The proposed integration of resources will have a major positive impact on the maternal–newborn dyad. Abstract : Fragmented‐care resource‐independent policies put the maternal–newborn dyad at high risk. Integration of healthcare resources even in low‐income countries can improve global dyad outcomes.